Master builder Roblox : the essential guide. (Chicago, IL: Triumph BooksLLC, 2018)
(Summary)"Master Builder Roblox: The Essential Guide" gives users an exciting introduction and jumpstart into the fascinating and dynamic world of Roblox, and helps guide kids toward a fun and fulfilling experience. Main topics include an introduction to the world, a tour of the coolest and most popular games within the game, a quick-start guide on how to build, and an overview of the Roblox Studio Tabs--the toolbox for building content in-game...
"Totally unauthorized" --cover./ "All you need to know to navigate, create & make great content" -- cover.
Keywords: Roblox (Computing platform); Video games -- Handbooks, manuals, etc